Fault analysis on elliptic curve cryptosystems with sliding window method - Jin-zhong ZHANG; Ying-zhan KOU; Tao WANG; Shi-ze GUO; Xin-jie ZHAO (Tongxin xuebao)
Based on the principle of sign change fault attacks,an improved fault analysis method was presented against elliptic curve cryptosystems with sliding window method for point multiplication.When faults on double instruction it could effectively solve the “zero block failure” problem.Experiment results demonstrate that 15 times fault injections are enough to recover full 192bit key.When faults on add instruction,a new fault analysis method was proposed.Experiment results demonstrate one fault injection can reduce searching space 27~215.The method presented here can provide some ideas for fault attack on other cryptosystems using sliding window method.